Implementasi Kebijakan Wajib Belajar Sembilan Tahun - Rupinus Rupinus; Arifin Arifin; Tora Akadira (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of Intellectual Capital on company value with financial performance as an intervening variable. The population in this study includes companies registered in LQ45 consecutively during the 2018-2022 period. The analysis technique applied is multiple linear regression and the Sobel test using financial performance as an intervening variable. The research results show that Intellectual Capital has a positive effect on Financial Performance, Financial Performance has a positive effect on Company Value, and Intellectual has no effect on Company Value. It is concluded that the results of this research prove that Intellectual Capital has a positive effect on Company Value and mediates Financial Performance. Keywords: Intellectual Capital, Financial Performance, Company Value.